Strategi Penguatan Branding Rintisan Desa Wisata Branjang Melalui Event Budaya Berbasis Kearifan Lokal “Branjangan - Krisnatalia, Heni; Tutik, Tutik; Satato, Y.R (Journal of Dedicators Community, 2023)
Creating and communicating the identity of a region is an effort to build a brand. This is done so that one's impression of the area changes, including changes in perspective in comparing one place to another to be chosen as a destination. Overall, this is what is familiarly referred to as destination branding. The basic concept of destination branding is based on passion and a unique and attractive identity that is tied to various things so that the inherent brand of a destination will be embedded in their minds. Strengthening destination branding aims to raise awareness of the existence of the Branjang Tourism Village as a tourist destination.